What change of variables would trtansform the logistic equation into the Mandelbrot equation $z_{n+1}=z_n^2+c$?

  • 1
    AND: since we have different answers here, the next step is to check your answer! – GEdgar Jan 30 '13 at 14:22
  • Since the OP is still present on the site, they might wish to answer my comment on @distantTransformer's answer below. – Did Sep 11 '13 at 16:45
up vote 0 down vote accepted

$$ z= i \cdot s \cdot (x - 0.5),\quad c = 0.5 \cdot \sqrt{s} $$

  • For the record, I do not understand this answer. If either the answerer or the author of the question could explain. – Did Feb 2 '13 at 10:48

Well, you can do the next trick:


$$f(sx_n(1-x_n))=f(x_{n+1})=z_{n+1}=z_n^2+c = f(x_n)^2+c$$

So we want our transformation to fulfill:

$$f(sx_n-sx_n^2)-(f(x_n))^2= c$$

I guess you can check for $$f(x)=Ax+B$$, and then solve to find $A,B$.

$$A(sx-sx^2)+B-(A^2x^2+2ABx+B^2) = c$$ Because this should be valid for all $x$, we should have: $$-As-A^2=0$$ $$-2BA+As=0$$ $$B-B^2=c$$ $A\neq 0$, thus: $A=-s$ and $B=s/2$, and we should also have $s/2-s^2/4=c$

Using the change of variable $z_n=s\cdot(\frac12-x_n)$ yields $z_{n+1}=z_n^2+c$ with $c=\frac12s-\frac14s^2$.

Your Answer


By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.